A PERFORMANCE ANALYSIS OF HYBRID SHE PWM VS. SHM PWM TECHNIQUES FOR HARMONICS CONTROL IN MULTILEVEL INVERTERS - Mazhar Ali,; Khalid Rehman,; Muhammad Nazzal Akbar,; Saad Ahmad,; Kiran Raheel, (Spectrum of Engineering Sciences, 2025)
A distinctive Multilevel Inverter arrangement has been meticulously designed to reduce the number of power electronic components. This inverter system emphasizes effective harmonic control by utilizing a technique which is Hybrid Modulation that integrates the SHE-PWM for Elimination Pulse Width Modulation and the SHM-PWM for Mitigation Pulse Width Modulation. Utilizing Fourier series expansion, the paper formulates six nonlinear equations. The proposed topology generates a quarter-wave odd symmetry output waveform, eliminating even harmonics and exclusively producing odd harmonics. For half-wave, specific harmonics are targeted for elimination or mitigation while maintaining the fundamental harmonic at its maximum. To resolve the six nonlinear equations, an objective function is designed and subjected to constraints, utilizing a Genetic Algorithm to determine optimal switching angles. This investigation will use a Genetic Algorithm (GA) to identify the best switching angles for the suggested topology and modulation strategy. Extensive simulation analyses and comparing indicate that this method works better than conventional multi-level inverters at similar levels. Particularly, compared to previous multi-level inverters operating at the same level, the suggested design achieves much reduced Total Harmonic Interference.